The Advances in Molecular and New Point-of-Care (POC) Diagnosis of Schistosomiasis Pre- and Post-praziquantel Use: In the Pursuit of More Reliable Approaches for Low Endemic and Non-endemic Areas - Cavalcanti, Marta G.; Cunha, Aline Fernandes Araujo; Peralta, José Mauro (Frontiers in Immunology, 2019)
Schistosomiasis is the second most important neglected tropical disease (NTD) in the world. Diagnosis of active infection is crucial for surveillance of controlled or post-elimination schistosomiasis areas. In addition, the use of conventional diagnostic tools in no-exposure populations (such as travelers and children 0–5 years old) results in misdiagnoses in the prepatent period of infection exposure. Also, the accuracy of standard tests applied in low-endemicity areas (LEAs) decreases after several treatment courses. We aimed to determine whether it would be necessary to replace the standard diagnostic tools completely. Reliable, cheap and easy-to-use diagnostic tools are needed to respond to the demands of a new era of global eradication of schistosomiasis. To this end, molecular diagnosis—including nucleic acid-based assays (loop-mediated isothermal amplification, polymerase chain reaction) and circulating cathodic and anodic antigen detection (POC-CCA, POC-CAA) point-of-care tests have become promising strategies. In this review, we attempt to address the use of alternative diagnostic tests for active infection detection and drug-monitoring after specific schistosomiasis treatment.